2018
DOI: 10.1371/journal.pone.0201569
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of qPCR versus culture for the detection and quantification of Clostridium difficile environmental contamination

Abstract: Contaminated surfaces serve as an important reservoir for Clostridium difficile transmission. Current strategies to detect environmental contamination of C. difficile rely heavily on culture, and often only indicate presence versus absence of spores. The goal of this study was to compare quantitative PCR (qPCR) to culture for the detection and quantification of C. difficile from inert surfaces. First, we compared the limit of detection (LOD) of a 16S rRNA gene and toxin B gene qPCR assay for detection of C. di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
9
1
Order By: Relevance
“…Since the detection of Clostridium by culture methods is insufficient [42], we employed PCR-amplification of bacterial DNA to determine the frequency of Clostridium in oral flora. In general, Clostridium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Since the detection of Clostridium by culture methods is insufficient [42], we employed PCR-amplification of bacterial DNA to determine the frequency of Clostridium in oral flora. In general, Clostridium spp.…”
Section: Discussionmentioning
confidence: 99%
“…In adult mice, we found that doses ranging from 1 × 10 4 to 1 × 10 6 CFU caused symptoms of C. difficile disease, including ruffled fur, hunched posture, and weight loss, with dose-dependent mortality ( Figure 1A). C. difficile intestinal burden was monitored by quantitative PCR (qPCR) analysis of the tcdB gene, as this approach is more sensitive than culturing (49) and detects endogenous strains of C. difficile found in some mouse strains (50,51). We found that C. difficile was absent in antibiotic-treated mice before infection, peaked on day 2, and then declined to nearly undetectable levels by day 8 after infection ( Figure 1B).…”
Section: Il-17 Is Efficiently Induced During C Difficile Infectionmentioning
confidence: 94%
“…C. difficile, C. perfringens, and E. faecium were detected in the fecal samples as previously described [37][38][39]. For E. faecium, 2 ng of fecal DNA was amplified with SYBR Green (Qiagen), and Efm12 [37] primers (GAAAGGACACGATTCTACTTGCT and ATG-AACGGAGCCCATCAAACC) were reacted at 94°C for 10 min, followed by 40 cycles of 94°C for 15 s and 60°C for 1 min.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…For E. faecium, 2 ng of fecal DNA was amplified with SYBR Green (Qiagen), and Efm12 [37] primers (GAAAGGACACGATTCTACTTGCT and ATG-AACGGAGCCCATCAAACC) were reacted at 94°C for 10 min, followed by 40 cycles of 94°C for 15 s and 60°C for 1 min. For C. difficile, primers and a probe (TTGAGCGATTTACTTCGGTA-AAGA, CCATCCTGTACTGGCTCACCT, and 6-FAM-CGGC-GGACGGGTGAGTAACG-MBG) [39] and qPCR Mastermix Plus (EUROGENTEC) were reacted at 50°C for 2 min and 95°C for 10 min, followed by 50 cycles of 95°C for 15 s and 60°C for 1 min. For C. perfringens, primers Clper [38] (GGGGGTTTCAA-CACCTCC and GCAAGGGATGTCAAGTGT) and SYBR Green were reacted at 95°C for 5 min, followed by 50 cycles of 94°C for 15 s and 60°C for 1 min.…”
Section: Real-time Pcrmentioning
confidence: 99%